PENDAMPINGAN SHADOW TEACHER DALAM PEMBELAJARAN INKLUSIF SEKOLAH DASAR BERBASIS PSIKOLOGI ISLAM - nurwidayanti (DEVELOPMENT: Journal of Community Engagement, 2025)
Inclusive education in elementary schools is more than simply placing students with special needs (ABK) in regular classes. Assistant teachers, who assist ABK in the learning process and social interactions, are key to the successful implementation of inclusive education. The purpose of this study was to examine the roles, challenges, and approaches to managing assistant teachers in elementary schools from an Islamic psychology perspective. The method used was a literature review, which included reading various books, journals, and other sources relevant to the research topic. The results revealed that the teachers under supervision function as learning facilitators, social mediators, and emotional supporters. These roles align with the concepts of ihsan (doing good), rahmah (compassion), and ta'awun (helping each other), which are the foundations of interpersonal relationships from an Islamic psychology perspective. A spiritual approach through patience (sabr) and sincerity (ikhlas) is essential for maintaining the mental well-being of assistant teachers. Successful management requires institutional support, a psychopedagogical approach (the science and techniques of teaching), and spiritual guidance. Keywords: Shadow Teacher, Inclusive Education, Elementary School, Islamic Psychology, Children with Special Needs